Time Management as a Foundation for Ethics, Integrity, Competence, Professionalism, and Communication in Higher Education Discipline - Muhammad Caesar Akbar; Ahmad Fakhrizal Pulungan; Darmeli Nasution; Bhadrappa Haralayya (Universitas Tribhuwana Tungga Dewi, 2025)
This research aims to analyze time management as an essential pillar in the development of ethics, integrity, competence, professionalism, and communication among students at Medan Aviation Polytechnic. Effective time management plays a vital role in developing a student's character, especially in forming the discipline that is the foundation of professional behavior in the aviation world. By adopting a qualitative approach, this research collected data through interviews, observations, and documentation studies of students and lecturers at the Medan Aviation Polytechnic. The research results indicate that effective time management plays a significant role in enhancing student ethics, integrity, and competence. Apart from that, time management also plays a crucial role in improving professionalism and effective communication, which are essential aspects in the aviation sector. This research offers recommendations for enhancing time management training within the higher education curriculum, aiming to foster students who are more disciplined and prepared to face future professional challenges. This is relevant to the needs of the aviation industry, which prioritizes punctuality, team coordination, and high adaptability in a dynamic work environment.Penelitian ini bertujuan untuk menganalisis manajemen waktu sebagai pilar penting dalam pembentukan etika, integritas, kompetensi, profesionalisme, dan komunikasi di kalangan mahasiswa Politeknik Penerbangan Medan. Manajemen waktu yang efektif berperan vital dalam pengembangan karakter mahasiswa, terutama dalam membentuk kedisiplinan yang menjadi dasar dari perilaku profesional di dunia penerbangan. Dengan mengadopsi pendekatan kualitatif, penelitian ini mengumpulkan data melalui wawancara, observasi, dan studi dokumentasi terhadap mahasiswa dan dosen di Politeknik Penerbangan Medan. Hasil penelitian menunjukkan bahwa manajemen waktu yang baik berkontribusi signifikan terhadap peningkatan etika, integritas, serta kompetensi mahasiswa. Selain itu, manajemen waktu juga berperan dalam meningkatkan profesionalisme dan komunikasi yang efektif, yang merupakan aspek penting dalam dunia kerja di sektor penerbangan. Penelitian ini memberikan rekomendasi untuk penguatan pelatihan manajemen waktu dalam kurikulum pendidikan tinggi, guna mendukung pengembangan karakter mahasiswa yang lebih disiplin dan siap menghadapi tantangan profesional di masa depan. Hal ini relevan dengan kebutuhan industri penerbangan yang mengutamakan ketepatan waktu, koordinasi tim, serta kemampuan adaptasi yang tinggi dalam lingkungan kerja yang dinamis.